Deception above, deception below: linking pollination and mycorrhizal biology of orchids - Waterman,RJ; Bidartondo,MI (Journal of Experimental Botany, 2008)
Several key characteristics of the species-rich orchid family are due to its symbiotic relationships with pollinators and mycorrhizal fungi. The majority of species are insect pollinated and show strong adaptations for outcrossing, such as pollination by food- and sexual-deception, and all orchids are reliant on mycorrhizal fungi for successful seedling establishment. Recent studies of orchid pollination biology have shed light on the barriers to reproductive isolation important to diversification in different groups of deceptive orchids. Molecular identification of orchid mycorrhizal fungi has revealed high fungal specificity in orchids that obtain organic nutrients from fungi as adults. Both pollinator and fungal specificity have been proposed as drivers of orchid diversification. Recent findings in orchid pollination and mycorrhizal biology are reviewed and it is shown that both associations are likely to affect orchid distribution and population structure. Integrating studies of these symbioses will shed light on the unparalleled diversification of the orchid family.